Some unpleasant fiscal arithmetic: the role of monetary and fiscal policy in public debt dynamics since the 1970s - Harri Hasko (Bank of Finland, 2007)
Shocks to monetary and fiscal policy have played a major role in public debt developments in the OECD countries since the mid-1970s. According to the applied VAR approach, these shocks, taken together, explained, on average, about half of the forecast error variation in the debt to GDP ratio, while the share of shocks to GDP growth was close to 30 percent. In contrast, shocks to inflation and the debt ratio itself played in most cases only a minor role. However, the inflation shocks were vital in initiating the public debt problems, as the increase in actual inflation, and particularly the persistence of high inflation expectations in the 1980s, led to a prolonged period of high real interest rates. Learning the implications of greater monetary discipline therefore gave rise to `some unpleasant fiscal arithmetic' which aggravated debt problems. In most countries fiscal policy aimed at correcting the deterioration in fiscal balances, but the progress was in most cases slow and delayed. It is noticeable that public debt developments have been quite similar in both the United States and the euro area despite differences in fiscal policy and the role of the public sector. Shocks to GDP growth, inflation and monetary policy, which have been more similar in both continents, explain about two thirds of the forecast error variation of the debt to GDP ratio, while shocks to fiscal policy explain about 20 percent.
URN:NBN:fi:bof-20140807598
Keywords: E62; H62; C22; 330; public debt dynamics; fiscal policy; monetary policy; VAR models